The Effectiveness of Several Sunscreen Products in Protecting Skin Exposed to Sun UV Rays - Lestiani Hulu; Desy Natalia Siahaan; Eva Sartika Dasopang; Fenny Hasanah (International Journal of Science and Society, 2026)
Sunscreen is a skincare product that functions to protect the skin from exposure to ultraviolet (UV) radiation, which can cause skin damage such as premature aging and hyperpigmentation. This study aims to compare the effectiveness and satisfaction level of using three sunscreen products from beauty clinics in Medan City, namely clinic A, clinic B, and clinic C. This study uses a quantitative approach with a quasi-experimental design. The research was conducted at Tjut Nyak Dhien University, Medan, with a total sample of 50 people. Measurements were taken using a Skin Analyzer (Aramo®) device and analyzed using the Paired T-Test to analyze the differences before and after treatment, along with the distribution of questionnaires for respondent satisfaction using the R-Studio software program. The results of the Paired T-Test showed that the negative control group experienced significant changes in all parameters (p < 0.05). The sunscreens from clinic A, clinic B, and clinic C also showed varying effectiveness. The sunscreen from clinic C showed significant changes in all parameters (p < 0.05), while the sunscreens from clinic A and clinic B did not show significant changes in the sensitivity parameter (p = 0.131 and p = 0.216, respectively). However, the sunscreen from clinic A had the highest preference score (39.10%).